Superresolution Imaging with Switchable Fluorophores Based on Oxazine Auxochromes1. (28th June 2013) - Petriella, Marco; Deniz, Erhan; Swaminathan, Subramani; Roberti, Maria J.; Raymo, Françisco M.; Bossi, Mariano L.
Abstract: The spatial resolution of fluorescence microscopes is limited by diffraction to about half of the light wavelength, hampering the observation of many important intracellular processes. Recent emerging techniques have overcome that diffraction barrier using the temporal discrimination of close objects that are otherwise unresolved or blurred within the spatial resolution of the microscope. The key of these techniques is to switch the signal of fluorescence markers on and off exploiting their distinct molecular states, and detect and localize these markers at the single‐molecule level. This underlying principle highlights the critical role of the photophysical properties of the probes, and the importance of finding adequate switching mechanisms. Here, we present strategies to achieve fluorescence modulation based on novel molecular assemblies containing a [1, 3]oxazine as the two states, building block responsible for the transformation. Two different triggering events, based on the photochromic and halochromic properties of the oxazine, induce a large absorption and emission bathochromic shift of a pendant fluorophore, as the ultimate fluorescence switching event. The implementation of these approaches to achieve spatial resolution beyond the diffraction limit is also discussed. Abstract : We present two alternative strategies to achieve controllable fluorescence modulation, based on a molecular assembly containing a [1, 3]oxazine, for imaging with a spatial resolution below the diffraction limit in single‐molecule localization fluorescence microscopies. The oxazine acts as a two‐state, a dark and a bright one, molecular switch. The incorporation of the assemblies in micelles renders them compatible for cellular biology applications.